Moving towards Decent Work. Labour in the Lula government: reflections on recent Brazilian experience - Paulo Eduardo de Andrade Baltar; Anselmo Luís dos Santos; José Dari Krein; Eugenia Leone; Marcelo Weishaupt Proni; Amilton Moretto; Alexandre Gori Maia; Carlos Salas (International Labour Organization (ILO), 2010)
In recent years, Brazil has seen an increase in formal employment, the raising of the minimum wage, a recovery in the purchasing power of the average wage, a drop in open unemployment and curbs on unprotected subcontracting. Average household incomes have risen and poverty has declined. How was this achieved? This paper argues that a minimum wage revaluation policy, broader social security coverage, income transfers and improved wage bargaining have all contributed to a reduction in inequality. The shift in labour market indicators is, they believe, conditioned by Brazil's economic dynamics, public policy on the raising of incomes, and a legal and institutional framework in which the public institutions and the trade unions play a prominent role. The authors advocate the creation of a development model that distributes income and dignifies citizens.
Keywords: 330